2010
DOI: 10.1186/1471-2210-10-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of silkworms for identification of drug candidates having appropriate pharmacokinetics from plant sources

Abstract: BackgroundWe use silkworms to evaluate therapeutic effects of drug candidates. Our previous reports have revealed that there are common mechanisms of pharmacokinetics of chemicals in silkworms and mammals. In this report, we attempt to establish a method by using silkworms to identify chemicals from plant extracts which are absorbed from intestine and also stably exist in body fluids.ResultsThree compounds were detected in the silkworm hemolymph by HPLC analysis after midgut injection of acetone extracts of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…We previously reported that therapeutic effects and pharmacokinetics of chemicals, such as antibacterial, anti-fungal, anti-viral drugs, in silkworm were similar to that in mammals (3,4,(7)(8)(9)(10). Silkworm can be easily handled for evaluation of therapeutic activities of drug candidates using large numbers of individual animals with low costs.…”
Section: Usefulness Of Silkworms For Evaluation Of Therapeutic Effectmentioning
confidence: 99%
“…We previously reported that therapeutic effects and pharmacokinetics of chemicals, such as antibacterial, anti-fungal, anti-viral drugs, in silkworm were similar to that in mammals (3,4,(7)(8)(9)(10). Silkworm can be easily handled for evaluation of therapeutic activities of drug candidates using large numbers of individual animals with low costs.…”
Section: Usefulness Of Silkworms For Evaluation Of Therapeutic Effectmentioning
confidence: 99%
“…Silkworm hemolymph and tissue can be harvested separately and used in biochemical, haematological, and immunological analyses [7,8]. Thus, the silkworm is an invertebrate model that can relieve the issues related to the use of mammals and thus promote pharmaceutical studies [7,9-12]. We previously demonstrated that the lethal dose of various cytotoxic substances in silkworms is consistent with that in mammals [7].…”
Section: Introductionmentioning
confidence: 99%
“…Different models of the silkworm have already been established: bacterial infection model (13,14), baculoviral infection model (15), model to test innate immunity (16)(17)(18), diabetic model (19), bacterial virulence model (20)(21)(22), model to test pharmacokinetics (23), and model to test toxicity and metabolism (24). Most of these research projects have proven the correlation between results in mammals and silkworms.…”
mentioning
confidence: 99%